Using LBB Tools to Assess Miter Squid Stock in the Northeastern South China Sea - Wang, Xuehui; He, Yinglin; Du, Feiyan; Liu, Mengna; Bei, Weilie; Cai, Yancong; Qiu, Yongsong (Frontiers in Marine Science, 2021)
Based on length frequency data of miter squid (Uroteuthis chinensis) collected in the northeastern South China Sea in 1975–1977, 1997–1999, and 2018–2019, asymptotic length, optimal length at first capture, relative mortality, and relative biomass of the stock were estimated using length-based Bayesian biomass estimation (LBB). The LBB-estimated asymptotic length for 2018–2019 was smaller. Optimal lengths at first capture for the later far exceeded average lengths in catches because of a major increase in fishing intensity. Between 1975 and 1977, relative total mortality (Z/K) was low, but it increased in the latter two periods, while relative natural mortality (M/K) showed a downward trend. Relative biomasses (B/B0 and B/Bmsy) indicated that the stock was close to unexploited between 1975 and 1977, but they declined to the levels of 6% and 4% in the later periods, which correspond to growth in fishing horsepower. Indeed, by 2018, fishing horsepower increased by nearly four times the optimal level. The analysis suggests that the stock of miter squid has been overfished since the mid-1980s and is now under heavy fishing pressure. To recover the stock, it is imperative to reduce fishing intensity and enforce size-at-first-capture regulations.